Pendampingan Implementasi Pelayanan Perizinan Beru Saha Terintegrasi Secara Elektronik Online Single Submission pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Banggai - Ririn Mahruf; Ismawati Doembana; Syaika Yanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In order to accelerate and increase investment and business capital, Government Regulation Number 24 of 2018 concerning Electronic Integrated Business Licensing Services was drafted. Based on this policy, all service permits try to be integrated by the center through one system, namely Online Single Submission (OSS). OSS is a licensing service system that aims to streamline licensing efforts and create an integrated licensing service model that is fast, cheap and provides certainty. The Banggai Regency Investment and One-Stop Integrated Services Service is one of the regional government agencies in Banggai Regency which implements a one-stop service system as an official agency specifically tasked with providing licensing services that directly touch the community, one of which is the Business Licensing Service through OSS. The aim of implementing this activity is to provide strengthening of the apparatus in improving the quality of Business Licensing Services through OSS efficiently and effectively. The implementation method used in this activity is using a mentoring method aimed at the Banggai Regency Investment and One Stop Integrated Services Service. The implementation includes several stages, namely starting from observation, coordinating with officers in the Licensing and Business Services sector, then assistance is carried out at the office of the Investment and One-Stop Integrated Services Service, accompanied directly by officers. The results of the implementation of the Electronically Integrated Online Single Submission (OSS) Business Licensing Service at the Banggai Regency One Stop Integrated Service Investment Service have been implemented, but there are still obstacles in conveying information that have not been fully accepted by the public. Through this activity, it is hoped that it can improve the quality of the Implementation of Business Licensing Services through (OSS).